Establishment and Characterization of a Novel Cell Line, ASAN-PaCa, Derived From Human Adenocarcinoma Arising in Intraductal Papillary Mucinous Neoplasm of the Pancreas. Issue 10 (November 2016) - Heller, Anette; Angelova, Assia L.; Bauer, Sonja; Grekova, Svitlana P.; Aprahamian, Marc; Rommelaere, Jean; Volkmar, Michael; Janssen, Johannes W.G.; Bauer, Nathalie; Herr, Ingrid; Giese, Thomas; Gaida, Matthias M.; et al.
Abstract : Objectives: Our aim was to establish and characterize a novel pancreatic ductal adenocarcinoma cell line from a patient in whom the origin of the invasive carcinoma could be traced back to the intraductal papillary mucinous neoplasm (IPMN) precursor lesion. Methods: The primary patient-derived tumor was propagated in immunocompromised mice for 2 generations and used to establish a continuous in vitro culture termed ASAN-PaCa . Transplantation to fertilized chicken eggs confirmed the tumorigenic potential in vivo. Molecular analyses included karyotyping, next-generation genomic sequencing, expression analysis of marker proteins, and mucin-profiling. Results: The analysis of marker proteins confirmed the epithelial nature of the established cell line, and revealed that the expression of the mucin MUC1 was higher than that of MUC2 and MUC5AC. ASAN-PaCa cells showed rapid in vitro and in vivo growth and multiple chromosomal aberrations. They harbored mutations in KRAS (Q61H), TP53 (Y220C), and RNF43 (I47V and L418M) but lacked either IPMN-specific GNAS or presumed pancreatic ductal adenocarcinoma–driving mutations in KRAS (codons 12/13), SMAD, and CDKN2A genes. Conclusions: ASAN-PaCa cell line represents a novel preclinical model of pancreatic adenocarcinoma arising in the background of IPMN, and offers an opportunity to study how further introduction of known driver mutations might contribute to pancreatic carcinogenesis.